Compressive hematoma and deep arteriovenous malformation: Emergency endovascular occlusion via a venous approach with surgical evacuation of the hematoma. Issue 1 (February 2016) - Sedat, Jacques; Chau, Yves; Sachet, Marina; Cattet, Florian; Lonjon, Michel
Compressive hematoma associated with deep arterio-venous malformation is a difficult surgery. Arterial presurgical embolization is often indicated but rarely effective. Endovascular occlusion via a venous approach is a technique that has recently been undertaken successfully to treat certain types of sub-pial vascular malformation. The venous endovascular approach has succeeded in a 20-year-old man of who presented with a compressive hematoma due to rupture of a deep arteriovenous malformation. By fully endovascular occlusion, the surgery consisted of surgical removal of the hematoma, with reduced cortical damage.